Adjusting maternal mortality data for international comparisons. The case of vital registration systems - Susie Jentoft; Vibeke Oestreich Nielsen; Dag Roll-Hansen (Statistics Norway, Research Department, 2014)
Register data on maternal deaths is adjusted in international reports to account for underreporting; however, there has been controversy around these adjustments. The objective of this article is to review the adjustment factors applied to maternal mortality register data. A literature review provided 72 studies on underreporting showing differences in the definition of maternal mortality. This has not previously been taken into account when calculating average adjustment factors. Our analysis showed that including psychiatric disease and maternal deaths occurring 42 days post-partum had significant effects on the adjustment factor. When using the strict WHO definition of maternal mortality, a median adjustment factor of 1.5 was calculated which is identical to the one used by the WHO. Guidelines on inclusion criteria for maternal deaths need to be clarified in order for figures to be internationally comparable.
Keywords: I18; 330; Maternal mortality ratio (MMR); Misclassification; Underreporting; Incompleteness; World Health Organisation (WHO)